DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE PRESCHOOL TEACHERS AS A SUBJECT OF SCIENTIFIC RESEARCH (Psychology Travelogs, 2023)
The article reveals the content of the concept of "professional competence of future preschool teachers". It is emphasized that the study of the problem of professional competence of the future teacher remains a relevant and important direction of research in the field of preschool education. The results of the analysis of scientific literature allowed to define it as a set of competencies necessary for the effective activity of a preschool teacher, namely psychological and pedagogical, general cultural and methodological.The data of the ascertaining experiment proved the need to develop the professional competence of future preschool teachers Among the students' answers to the question: "What, in your opinion, does the concept of "professional competence of future teachers of preschool education institutions include?": the following prevailed: readiness to act in non-standard situations, possession of heuristic methods of problem solving, ability to independently solve educational and cognitive tasks, creativity, mobility, social and professional responsibility.The article substantiates the psychological and pedagogical conditions (taking into account the requirements of the competence approach and the peculiarities of the professional activity of future teachers of preschool education institutions; development of positive motivation of students through their participation in various types of practice; modeling situations of independent cognitive activity in order to develop intellectual and cognitive skills) for the development of professional competence of future teachers of preschool education institutions.For each group of professional competencies, the most effective forms and methods of their development were identified. The program was implemented through group and individual forms of work with students - future teachers of preschool education institutions.
Keywords: competence; professional competence; professional competence of future preschool teachers; psychological and pedagogical conditions